2012
DOI: 10.1021/ar300047s
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimensional Soft Material: New Faces of Graphene Oxide

Abstract: Graphite oxide sheets, now called graphene oxide (GO), can be made from chemical exfoliation of graphite by reactions that have been known for 150 years. Because GO is a promising solution-processable precursor for the bulk production of graphene, interest in this old material has resurged. The reactions to produce GO add oxygenated functional groups to the graphene sheets on their basal plane and edges, and this derivatization breaks the π-conjugated network, resulting in electrically insulating but highly wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
389
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(394 citation statements)
references
References 44 publications
4
389
0
1
Order By: Relevance
“…The introduction of oxygen-containing groups (such as hydroxyl, epoxy, carbonyl and carboxyl groups) [5] can increase the hydrophilic ability of GO. With large content of functional groups, GO could form stable single-layer suspensions in water or other common polar solvents [6].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of oxygen-containing groups (such as hydroxyl, epoxy, carbonyl and carboxyl groups) [5] can increase the hydrophilic ability of GO. With large content of functional groups, GO could form stable single-layer suspensions in water or other common polar solvents [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the use of highly dispersed liquid crystalline GO (LCGO), a graphene precursor that can be readily processed and fabricated into a wide variety of structures using a number of different 3D fabrication methods, offers significant advantages. 4,28 The LCGO nanoplatelets are more than 10 times larger than the typical GO nanoplatelets affording highly ordered structures in solution and thus more viscous solutions for processing and fabrication. These larger nanoplatelets result from oxidation of natural graphite.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] They have been studied for fuel cell applications as an additive to proton exchange membranes by several groups since 2012. Choi et al prepared GO/Nafion membranes for DMFC applications and found that the transport properties of Nafion are favorably modified by the incorporation of GO, which greatly enhanced fuel cell performance.…”
mentioning
confidence: 99%